Anaerobic co-digestion of dissolved air floatation slurry and selenium rich wastewater for simultaneous methane production and selenium bioremediation. (August 2022) - Logan, Mohanakrishnan; Tan, Lea Chua; Lens, Piet N.L.
Abstract: The energy potential of dissolved air floatation (DAF) slurry, a lipid-rich waste, is largely disregarded with the common practice of land spreading or landfilling. On the other hand, selenium (Se) contaminated wastewaters are perceived as unsuitable feedstocks because of their toxicity. This study aimed to evaluate the anaerobic co-digestion performance of a DAF slurry with Se rich wastewater using anaerobic granular sludge and waste activated sludge as the inocula. Anaerobic batch assays of DAF slurry supplemented with 0.05, 0.10, 0.25 and 0.50 mM selenate (SeO4 2− ) and selenite (SeO3 2− ), along with a control (without Se) were performed at 30 °C. Methanogenesis of the DAF slurry using anaerobic granular sludge was realised during co-digestion up to 0.50 mM SeO4 2−, whereas SeO3 2− was already toxic from 0.05 mM onwards. Co-digestion of the DAF slurry with 0.05 and 0.10 mM Se oxyanions (both selenate and selenite) containing wastewater using waste activated sludge achieved a similar cumulative methane yield of about 180 mL/g COD as that of mono-digestion (Se free DAF slurry) after 65 days of incubation. Simultaneously, more than 90% removal of Se was accomplished. The lag phase duration was, however, extended by 50 and 90% in the presence of 0.05 and 0.10 mM Se, respectively. The half maximal inhibitory concentration (IC50 ) for methane production using waste activated sludge was 0.08 mM for SeO4 2− and 0.07 mM for SeO3 2− . The IC50 amounted to 2.10 mM for SeO4 2− and 0.08 mM for SeO3 2− with anaerobic granular sludge. SeO4 2− and SeO3 2− were reduced to elemental Se nanoparticles, as shown by transmission electron microscopy. This study indicates the feasibility of methane production from a DAF slurry, codigested with wastewaters containing up to 0.10 mM SeO4 2− or SeO3 2− . Highlights: Methane recovery from DAF slurry supplemented with selenium oxyanions demonstrated. Methane yield of 180 mL/g COD unaffected when co-digested with 0.10 mM SeO4 2− or SeO3 2- . Lag phase prolonged by 50% at 0.05 mM Se and by 90% at 0.10 mM Se. SeO3 2− concentrations >0.10 mM inhibited methane production from DAF slurry.